THE TRANSFORMATION OF POLITENESS STRATEGIES INDIGITALDISCOURSE: A PRAGMATIC ANALYSIS - Sarimsakova ShoiraUlugbekqizi (International Journal of Literature and Language Studies, 2026)
This article investigates how politeness strategies are changinginthedigital age due to the rise of online communication. While traditional politeness relies onface-toface cues like tone of voice and gestures, digital communication lacks these physical elements.Using a corpus of 45,000 words from academic and social media interactions, this articleanalyzeshow people adapt. The results show that digital politeness is a highly structuredsystem.Interlocutors systematically use emojis as pragmatic softeners to reduce the bluntnessoftextmessages. Additionally, the study identifies chronemic hedging intentionally delayingresponsesasa new way to show respect for another person’s time